PSYCHOLOGICAL NEEDS FOR SENSE OF PLACE AND PERSONAL SPACE IN PUBLIC AREA - Kumari, P.Meena (International Journal of Engineering Technologies and Management Research, 2018)
Environmental phycology and behavior in built environment is the field that interests the social scientists and environmental designers for many years. In-depth study and research finding are conducted and have discussed in detail the philosophy and the abstract theories on concept of privacy, personal space, sense of place by the people in a given built environment. As per Roger Barker (1951) statement, the paper proposes that the ecological environment does not demand much but permits some behavioral pattern to take place naturally and elucidate that the built environment tends to act as a catalyst in providing space for the users to perform but also act as a despot in making the users to alter their needs and behavior to the built setting. The paper also touches on the important issues in understanding, and translation of these psychological and behavioral theories and concepts into the real tangible substantial world that the architects and designers can imply upon. The fundamental primal need of people to have personal space and a sense of place in public area is reviewed in this paper and concludes for a cohesive way to achieve this ,by means of participation, cooperation and understanding among designers and environmental psychologists with the people.